The role of agile leadership in organizational excellence / analytical study in the Iraqi Ministry of Justice. - Jawad Kazem, Nora; Hassan Gomaa, Mustafa; Salem Muhammad, Yazan (Iraqi Journal for Administrative Sciences, 2024)
The research aims to identify the actual reality of graceful leadership and its role in achieving organizational excellence and its application in the Iraqi Ministry of Justice. Which was represented by agile leadership with its dimensions (self-confidence, vision, ideal influence) and its role in achieving organizational excellence by its dimensions (excellence in human resources, excellence in organizational structure, excellence in strategy, excellence in knowledge), the research problem was to ensure the existence of the relationship and the impact between agile leadership in organizational excellence in the Iraqi Ministry of Justice and to determine the correlational relationships between the research variables. Where the current research was based on the descriptive and analytical approach because it is more appropriate to the nature of the subject of the research, the questionnaire was used as a tool for collecting data and information related to the research, and the study population consisted of managers and their assistants in (8) departments of the surveyed ministry, which numbered (85), where a sample was chosen. An intentional stratified consisting of (45) principals representing the study community. And organizational excellence, and the research concluded with recommendations, the importance of the ministry in question showing the characteristics of agile leadership at work, and this consequently leads to an increase in the performance level of employees, an increase in the percentage of achievement, and the achievement of the requirements of organizational excellence.